Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1021/jp960312h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Diels−Alder Cycloadditions of Butadiene to C70. An Insight into the Chemical Reactivity of C70 as Compared to C60

Abstract: The eight unique Diels-Alder cycloadditions of butadiene to C 70 are analyzed theoretically and compared with the well-established, two possible Diels-Alder cycloadditions of butadiene to C 60 . Full geometry optimizations of reactants, adducts, and transition states are performed using the AM1 semiempirical method followed by single-point ab initio energy calculations. The results show that the cycloaddition of butadiene to the C 70 fullerene in the gas phase is slightly more reactive than that to C 60 . Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 80 publications
10
59
2
Order By: Relevance
“…We used this semiempirical method instead of a more accurate ab initio method to compute the geometries for several reasons: first, the sizes of some of the systems studied prevented the use of ab initio molecular quantum-mechanical methods to perform optimizations, second, we have found by comparison with our previous results for C 6 H 6 , C 10 H 8 , and C 14 H 8 [73] that differences in HOMA, NICS, and PDI indices computed at the HF/6-31G* (HOMA and PDI) and HF/6-31 G* (NICS) levels by use either of the B3LYP/6-31G* or of the AM1 geometries are generally small, and third, the AM1 method yields reliable results for the geometries of C 60 , [87,88] C 70 , [88] and also for the series of PAHs studied. We used this semiempirical method instead of a more accurate ab initio method to compute the geometries for several reasons: first, the sizes of some of the systems studied prevented the use of ab initio molecular quantum-mechanical methods to perform optimizations, second, we have found by comparison with our previous results for C 6 H 6 , C 10 H 8 , and C 14 H 8 [73] that differences in HOMA, NICS, and PDI indices computed at the HF/6-31G* (HOMA and PDI) and HF/6-31 G* (NICS) levels by use either of the B3LYP/6-31G* or of the AM1 geometries are generally small, and third, the AM1 method yields reliable results for the geometries of C 60 , [87,88] C 70 , [88] and also for the series of PAHs studied.…”
Section: Resultsmentioning
confidence: 86%
“…We used this semiempirical method instead of a more accurate ab initio method to compute the geometries for several reasons: first, the sizes of some of the systems studied prevented the use of ab initio molecular quantum-mechanical methods to perform optimizations, second, we have found by comparison with our previous results for C 6 H 6 , C 10 H 8 , and C 14 H 8 [73] that differences in HOMA, NICS, and PDI indices computed at the HF/6-31G* (HOMA and PDI) and HF/6-31 G* (NICS) levels by use either of the B3LYP/6-31G* or of the AM1 geometries are generally small, and third, the AM1 method yields reliable results for the geometries of C 60 , [87,88] C 70 , [88] and also for the series of PAHs studied. We used this semiempirical method instead of a more accurate ab initio method to compute the geometries for several reasons: first, the sizes of some of the systems studied prevented the use of ab initio molecular quantum-mechanical methods to perform optimizations, second, we have found by comparison with our previous results for C 6 H 6 , C 10 H 8 , and C 14 H 8 [73] that differences in HOMA, NICS, and PDI indices computed at the HF/6-31G* (HOMA and PDI) and HF/6-31 G* (NICS) levels by use either of the B3LYP/6-31G* or of the AM1 geometries are generally small, and third, the AM1 method yields reliable results for the geometries of C 60 , [87,88] C 70 , [88] and also for the series of PAHs studied.…”
Section: Resultsmentioning
confidence: 86%
“…We have used the Austin model 1 (AM1) semiempirical method 44 as implemented in Gaussian 98 45 to perform geometry optimizations within the restricted formalism. We previously showed that the AM1 method yields reliable results for the geometries of C 60 46, 47 and C 70 47. Calculations of delocalization indices have been carried out using the ab initio Hartree–Fock (HF) method with the 6‐31G* basis set 48–50 at the AM1‐optimized geometries (HF/6‐31G*//AM1) by means of the AIMPAC collection of programs 51.…”
Section: Methodsmentioning
confidence: 99%
“…1), with the most reactive being the 1-2 and 5-6 bonds [42] in this order [43]. This fact is supported by theoretical calculations, which show that the product in the 1-2 position is the most stable, followed by the 5-6 isomer [44]. Several reports have indicated that C 60 and C 70 differ in their rates of reactivity.…”
Section: Azomethine Ylidesmentioning
confidence: 53%